# Let f(x) = x − 2 and g(x) = x^{2} − 7x − 9. Find f(g(−1)).

We will use the concept of functions to solve this.

## Answer: If f(x) = x − 2 and g(x) = x^{2} − 7x − 9, then f(g(-1)) is -3.

Let us solve it step by step.

**Explanation:**

Given that:

f(x) = x − 2 ---------- (1)

g(x) = x^{2} − 7x − 9 ----------- (2)

Both f(x) and g(x) are function of x and depend on x.

We have to find composite function f(g(x))

f(g(x)) = {g(x)} - 2

f(g(x)) = (x^{2} − 7x − 9) - 2 [From (1) and (2)]

f(g(x)) = x^{2} − 7x − 11

Now let us solve this for x = -1.

f(g(-1)) = (-1)^{2} − 7(-1) − 11

f(g(-1)) = 1 + 7 -11

f(g(-1)) = -3